Quality Improvement and By-product Utilization in Dry-Fermented Catfish Processing: A Case Study of Ban Chumphon Community Enterprise, Phatthalung Province, Thailand - Klompong, Vilailak; Klomklao, Sappasith; Mayachiew, Pornpimon; Luanunkarb, Thanidchaya; Hoktha, Pimchana; Thanonkaew, Amonrat (Area Based Development Research Journal, 2025)
Ban Chumphon Community Enterprise, located in Srinakarin District, Phatthalung Province, has long been engaged in the production of dry-fermented catfish, a traditional Thai fermented fish product. Despite the economic potential of this industry, the enterprise has faced numerous challenges, including non-compliance with Good Manufacturing Practices (GMP) and Thailand’s Food and Drug Administration (FDA) regulations, limited product diversity, inefficient utilization of processing by-products, suboptimal packaging, restricted market reach, and low brand recognition. These challenges have hindered the growth and sustainability of the enterprise, limiting its ability to expand into broader markets and improve its profitability. To address these issues, this study was undertaken with the following objectives: (1) to improve the dry-fermented catfish production process to meet GMP standards and obtain FDA certification, and (2) to promote technology transfer through community participation, with a focus on developing ready-to-eat products and maximizing by-product utilization. The study employed an area-based participatory approach, engaging local producers, experts, and stakeholders to ensure that the solutions were practical, sustainable, and aligned with community needs. The research was structured into five key steps: (1) upgrading production processes to comply with GMP standards, (2) analyzing the chemical and biological properties of dry-fermented catfish products to ensure safety and quality, (3) implementing technology transfer initiatives through workshops and training sessions, (4) obtaining FDA certification for new and existing products, and (5) enhancing packaging and label design to improve market appeal. One of the primary focuses of this initiative was the improvement of the production environment and methods. The facility underwent significant modifications to align with GMP standards, including the redesign of processing areas to ensure hygiene, the implementation of standard operating procedures, and the introduction of quality control measures to maintain product consistency. These enhancements led to the successful establishment of a GMP-compliant production facility and the issuance of a food production license by the Phatthalung Provincial Public Health Office. In parallel with the production process improvements, the study also explored the chemical and microbiological characteristics of dry-fermented catfish to validate its safety, nutritional value, and potential for extended shelf life. Laboratory analyses confirmed that the improved production methods resulted in safer products with consistent quality, reinforcing consumer confidence and regulatory compliance. Beyond compliance and quality assurance, the study emphasized value addition and by-product utilization. Traditionally, catfish processing generates substantial waste, including fish bones and fermentation broth, which are often discarded. Through technology transfer initiatives, the community was trained in innovative methods to transform these by-products into commercially viable products. Five new value-added products were developed as a result: (1) dry-fermented catfish chili paste, (2) rice seasoning derived from catfish bones, (3) ready-to-eat fried dry-fermented catfish, (4) Khao-Yum sauce formulated from fermentation broth, and (5) sweet fish sauce also derived from fermentation broth. These products not only minimized waste but also expanded the product line, creating new revenue streams for the community enterprise. The success of these new products was further enhanced by strategic packaging and branding improvements. Previously, the enterprise faced difficulties in attracting consumers due to unattractive packaging and inconsistent labeling. To address this, packaging designs were upgraded with clearer nutritional information, appealing visuals, and compliance with FDA labeling regulations. These changes contributed to greater product recognition, increased consumer trust, and an expanded market presence. The impact of these interventions was substantial. Following the implementation of the project, six of the enterprise’s products received FDA certification, validating their safety and quality. Additionally, production capacity saw a dramatic increase, tripling from 200 kg to 600 kg per month. The introduction of new products, such as dry-fermented catfish chili paste and sweet fish sauce, further boosted sales, leading to a significant revenue increase from 24,000 to 99,000 Bath per month—representing a remarkable 312.5% growth. These improvements enabled the community enterprise to diversify its market channels, including local markets, online sales, and retail partnerships, enhancing long-term business sustainability. Beyond economic benefits, the project fostered knowledge-sharing and skill development among community members. Through training programs and participatory workshops, local producers gained technical expertise in food safety, processing innovations, and business development strategies. This empowerment strengthened the capacity of the community to sustain and further expand its dry-fermented catfish production in the long run. In conclusion, this study highlights the effectiveness of a participatory, technology-driven approach in revitalizing traditional food enterprises. By addressing key production challenges, ensuring regulatory compliance, and maximizing by-product utilization, the Ban Chumphon Community Enterprise successfully enhanced the quality, safety, and marketability of its dry-fermented catfish products. The integration of technology transfer, community engagement, and value-added innovations has demonstrated a viable model for other small-scale food enterprises seeking sustainable growth. Future initiatives could explore further advancements in product diversification, digital marketing strategies, and supply chain optimization to strengthen the competitiveness of traditional fermented fish products in both domestic and international markets.